High gain S-band semiconductors optical amplifier with double-pass configuration - Ahmad, Harith; Zulkifli, Mohd Zamani; Hassan, Nor Ahya; Latif, Amirah Abdul; Harun, Sulaiman Wadi (IOP Publishing, 2011)
In this paper we propose and demonstrate a double-pass configuration of a compact high gain short wavelength (S-) band amplifier based on a semiconductor optical amplifier (SOA) operating from 1480 to 1520 nm. The proposed system provides gain value of 31.07 dB at a signal power level of -40 dBm taken at 1500 nm. The measure gain profile of the double-pass configuration over different power levels and at different signal wavelengths outperforms that of the single-pass configuration. The noise figure of both configurations averages out to 10 dB. This system provides a good alternative as a high-gain and compact amplifier in the S-band region.